OP0290 Ox40l Blockade Protects against Skin and Lung Inflammation-Driven Fibrosis. (15th July 2016) - Elhai, M.; Avouac, J.; Hoffmann-Vold, A.-M.; Sadoine, J.; Guilbert, T.; Akiba, H.; Heissmeyer, V.; Subramaniam, A.; Resnick, R.; Chiocchia, G.; Allanore, Y.
Abstract : Background: Systemic sclerosis (SSc) is a severe fibrotic disease with no effective treatment. The OX40-OX40L axis is emerging as a new potential target in autoimmune diseases offering the advantage of a targeted approach on co-stimulatory signals with limited impact on the whole immune response and very preliminary data suggested its involvement in SSc. Objectives: To investigate the contribution of OX40L in SSc Methods: We assessed the expression of OX40L in fibrotic skin and in the serum of SSc-patients. The efficacy of a targeted therapy against OX40L in vivo was evaluated using complementary experimental mouse models. Results: Expression of OX40L protein was higher in fibrotic skin of SSc-patients as compared to healthy controls (p=0.003), particularly in diffuse cutaneous forms. Soluble OX40 levels were significantly higher in SSc-patients (n=177) than in healthy controls (n=100). Longitudinal analyses of our cohort showed that high level of serum OX40L at baseline was highly predictive of worsening of dermal and lung fibrosis during the follow-up (HR: 8.28 [2.11–32.50] and 4.60 [1.52–12.18], P<0.001). This was confirmed in a replication Norwegian cohort (n=241) dedicated to lung fibrosis analysis. In this cohort, in multivariate analyses, OX40L was a strong predictor of lung fibrosis including known risk factors for lung fibrosis. Invalidation of OX40L prevented dermal fibrosis in the bleomycin mouse model with a decrease in dermal thickness, hydroxyprolin content and myofibroblasts count. OX40L invalidation was associated with a decrease in T cell, B cell and macrophage infiltrates and in cytokine release (IL-6, TNF-α) in lesional skin of mice. A transcriptomic approach identified two main pathways regulated by OX40L blockade: NF kappa B and AP 1 signaling. Then pharmacologic approaches, using a monoclonal anti-OX40L antibody, demonstrated that the blockade of OX40L not only prevented dermal fibrosis, but also induced regression of established fibrosis. Thereafter, the use of this monoclonal antibody demonstrated in the fra-2 transgenic mouse model marked protection from fibrosing alveolitis (measured by CT-scan (Figure ) and histology) and vessel remodeling leading to pulmonary arterial hypertension. Conclusions: Altogether, our results show that OX40L is as an attractive target in inflammation-driven fibrosis. OX40L appears as a very promising biomarker in SSc and an appealing potential therapy to reduce both skin and lung fibrosis. Disclosure of Interest: None declared